The Effect of Quva (Quiz Canva) Learning Media on The Interest In Learning Social Studies of Grade V Elementary Students - Farah Ajeng Meydista; Ika Yatri (Eduvest - Journal of Universal Studies, 2024)
Education is an important key in shaping individuals who are useful to the community, nation and state. Every individual has the right to receive a fair and comprehensive education. As technology develops, computerized learning becomes more effective and diverse. Canva, a popular visual design platform, can be utilized as an interactive learning tool to increase students' interest in learning. This study aimed to examine the impact of QuVa (Quiz Canva) media on social studies learning interest among fifth grade students at SDN Depok Jaya I. The study used a quasi-experimental method with two participants. The study used a quasi-experimental method with two classes: experimental using QuVa and control using conventional methods. Data was collected through pre-test and post-test. Based on the results, the experimental class experienced a clear increase in learning interest with the average post-test value reaching 47.00, while the control class only reached 37.50. T-test analysis showed a significance of 0.000 (p < 0.05), indicating that the use of QuVa media had a significant effect on students' social studies learning interest. In conclusion, the use of QuVa is effective in increasing social studies learning interest, creating interesting, interactive learning, and increasing student participation during the learning process.